2014
DOI: 10.1086/670811
|View full text |Cite
|
Sign up to set email alerts
|

Island Life Shapes the Physiology and Life History of Eastern Bluebirds (Sialia sialis)

Abstract: Island organisms face a range of extrinsic threats to their characteristically small populations. Certain biological differences between island and continental organisms have the potential to exacerbate these threats. Understanding how island birds differ from their continental relatives may provide insight into population viability and serve as a predictive tool for conservation efforts. We compared an eastern bluebird population in Ohio with a threatened population in Bermuda in terms of the birds' developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Furthermore, while varying substantially among individual nestlings, the indices did not significantly covary with nest index or rain within Kedong. The reliance on measurements at a single time point (i.e., day 10) can complicate comparisons among locations and through time, since the immune systems of nestlings, including components measured in the current study, may develop at different rates across individuals or populations e.g., [69]. Immunity of nestlings may partly reflect the immunological status of their parents [38, 39, 70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while varying substantially among individual nestlings, the indices did not significantly covary with nest index or rain within Kedong. The reliance on measurements at a single time point (i.e., day 10) can complicate comparisons among locations and through time, since the immune systems of nestlings, including components measured in the current study, may develop at different rates across individuals or populations e.g., [69]. Immunity of nestlings may partly reflect the immunological status of their parents [38, 39, 70].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial studies of urbanization can also test how defence differs between island and mainland populations. Passerine studies have tested the prediction that islands have lower parasite pressure that, in turn, lowers immune investment (Lindström, Foufopoulos, Pärn, & Wikelski, ), although comparative and case studies have found weak or opposite patterns (Matson, ; Matson, Mauck, Lynn, & Irene, ). As urbanization can reduce connectivity (Munshi‐South & Kharchenko, ), urban–rural sampling gradients could provide additional assessments.…”
Section: Future Directions For Macroimmunologymentioning
confidence: 99%
“…White-footed mice do not display island syndrome in the Thousand Islands Despite the tendency for island wildlife to display morphological and physiological adaptations to insularity (Matson et al, 2014;Holding et al, 2014;Spencer et al, 2017), white-footed mice in the Thousand Islands did not differ in any of these characteristics from their mainland conspecifics. White-footed mice on islands did not display higher relative abundance than mainland mice in disagreement with the general prediction that rodents exhibit particularly high densities on islands (Adler & Levins, 1994;Crespin, Duplantier & Granjon, 2012;, which has been observed for other small vertebrates as well (Novosolov, Raia & Meiri, 2013;Sale & Arnould, 2013).…”
Section: Discussionmentioning
confidence: 88%